Prevalence and correlates of major depression in Granada, Spain: Results from the GranadΣp study. (August 2018) - Porras-Segovia, Alejandro; Valmisa, Eulalio; Gutiérrez, Blanca; Ruiz, Isabel; Rodríguez-Barranco, Miguel; Cervilla, Jorge
Background: Major depression is one of the world's leading causes of disability. Up-to-date information about the epidemiology of this disorder is key to health care planning. Aim: The aim of our study is to report prevalence and correlates of current major depressive disorder (MDD) in the province of Granada, Southern Spain. Methods: The GranadΣp is a cross-sectional study based on a community-dwelling adult population living in the province of Granada, Southern Spain. Community-dwelling adults aged 18–80 years ( n = 810) were interviewed using the Mini-International Neuropsychiatric Interview (MINI). A variety of exposure assessments were also undertaken. Results: Point (2 weeks) prevalence of MDD in the Granada population was 5.6%. Positive family history of mental illness, high degree of neuroticism, high number of life threatening events (LTE), poor physical health status, cognitive impairment and cannabis use were independently associated with MDD in the multivariate regression model. Being female was also associated with MDD, but the significance disappeared after adjusting for neuroticism and physical health. Conclusion: Prevalence of MDD in the Granada population is higher than expected. The effects of the financial crisis could be partially accountable for this excess in prevalence. Six variables were found to be independently associated with MDD. Association between female sex and depression may be partially explained by the confounding effect of neuroticism.